Computerisation of trouble shooting in welding / Ahmad Asfanizam Mohamad and Mohd. Taufik Yusof - Mohamad, Ahmad Asfanizam; Yusof, Mohd. Taufik (Faculty of Mechanical Engineering, 1998)
The objective of this study is to generate a computer programme using “Q-BASIC” programming language in order to troubleshoot problems in welding. It is an information system to make our life easy without wasting our time to find the solution manually e.g. from handbooks, etc. The success of this study has been a combination from Q-BASIC advice, experience, textbooks, articles, application of what we have studied, and expert advice. Three (3) major criteria, or factors have been identified in this study using Basic in developing the rules. These are types of welding and their problems, causes of problems and the prevention of the problems.